PENGARUH KUALITAS PELAYANAN TERHADAP MINAT MENABUNG NASABAH (Studi Kasus pada Bank Sumsel Babel Cabang Tebing Tinggi) - Ari Cahyadi (Jurnal Media Ekonomi (JURMEK), 2017)
Service Qualilty is one of important factor in banking world. Most of the banking in Indonesia give a special attention to the quality service. The purpose of this research is to know the influence of Quality Sevice to Customer interest in saving on Sumsel Babel Bank Branch Of Tebing Tinggi. This research used quantitative descriptive method. Population in this research is all of saving costumer in Sumsel Babel Bank brach of Tebing Tinggi while the samples used is one hundred respondents with random sample retrieval techniques. Data retrieval techniques is used quisioner, while the data analysis technique is used multiple linear regression analysis, prerequisite test (normality test, multicollinearity test, linearity test) and statistic analysis (t test, f test, coefficient of determination). Result of this research is show that in partial, quality service variable is give an positif and significant influence, It mean if quality service variable is higher then make positif influence to Costumer Interest in Saving is Significant. This is supported by the result obtained form the correlation coefficient of 0,213 and partial significant test (t test) result t value are 2,162.